Keberlanjutan Korporasi Petani Jagung di Kabupaten Bandung, Jawa Barat - Puspita, Gusti Reza; Karyani, Tuti; Setiawan, Iwan (Analisis Kebijakan Pertanian, 2025)
The government has launched the corn farmer corporation program as a breakthrough in achieving food security. However, it is not known whether the program is competitive and sustainable for the long term or only an incidental program. This study aims to: a) analyze the sustainability dimensions of the corn farmer corporation program, which include economic, socio-cultural, environmental, technological, as well as legal and institutional dimensions; b) perform a Rap-Corn analysis to determine the sensitive attributes that affect the sustainability of corn farmer corporations; and c) determine the priority strategy based on the results of leverage analysis. This research was conducted in Bandung Regency, West Java Province. Data collection methods used in-depth interviews with six key informants and 81 respondents using a structured questionnaire. Data analysis used Multidimensional Scaling (MDS) with Rap-Corn coordination. The results of this study revealed that the economic (63.76%) and environmental (72.25%) dimensions were in the fairly sustainable category, while the socio-cultural (76.12%), technological (77.85%), and legal and institutional dimensions (83.01%) are in the very sustainable category. Ten sensitive attributes affect sustainability, including market access, farmer regeneration, access to irrigation, farmer response to new technology, and the existence of microfinance institutions (LKM). Strategies that need to be prioritized based on the results of the leverage analysis include 1) improving harvest and postharvest technology and 2) increasing farmer regeneration.